Real-time PCR analysis of age-dependent alterations in the RVLM neurotransmitter gene expression profile of F344 rats - Craig, Robin Ann (Kansas State University, 2007)
It is well established that normal aging is associated with progressive increases in efferent sympathetic nerve discharge (SND). Type II diabetes, obesity, heart failure, and hypertension are pathologies that have been attributed to both the processes of aging and sympathetic dysfunction, exemplifying the importance of understanding central regulation of SND during aging. However, the central mechanisms mediating altered SND with advancing age remain unclear. The rostral ventral lateral medulla (RVLM) is a brainstem region critically involved in setting the basal level of sympathetic outflow and cardiovascular function. Indeed, the RVLM is the only presympathetic region that when bilaterally inactivated results in profound reductions in both SND and arterial pressure. Glutamatergic influences in RVLM activity are powerfully inhibited by tonic GABAergic neural inputs originating from the caudal ventral lateral medulla (CVLM); effects that are mediated by GABAA receptors located on presympathetic neuronal cell bodies within the RVLM. In the present study we proposed that reductions in GABA[subscript A] receptor subunit gene expression may reflect withdrawal of GABAergic tone in the RVLM thereby contributing to the basal sympathetic activation that occurs with advancing age. Therefore, the objective of the current study was to identify age-related changes in the constitutive expression of genes related to GABAergic and muscarinic, nicotinic and dopaminergic receptor systems due to their reported involvement in modulating GABA[subscript A] receptor function, in the RVLM of adult young (3-5 mo. old), middle-aged (12 mo. old), weight stable presenescent (24-25 mo. old) and senescent (>24 mo. old) Fischer 344 (F344) rats using a commercially available real-time PCR array. Real-time analysis revealed nonuniform and age-associated changes in the RVLM GABA, muscarinic, nicotinic and dopaminergic neurotransmitter gene expression profile between young and middle-aged F344 rats. Heterogeneous expression of genes related to these neurotransmitters was also observed between presenescent and senescent F344 rats. Our results suggest that potential changes in neurotransmitter synthesis and degradation, uptake, transport, signaling and receptor subunit composition may account for the sympathoexcitatory state that is commonly observed in the aged.
Keywords: Rostral ventral lateral medulla; Fischer 344 rat; GABA; Aging; Sympathetic nervous system; Biology, Molecular (0307); Biology, Neuroscience (0317)